2010
DOI: 10.1080/10668926.2011.525185
|View full text |Cite
|
Sign up to set email alerts
|

Community College Student Success Courses: The Student Perspective

Abstract: This study explores student success courses from the student perspective to answer three questions: What topics do students find the most useful? What teaching methods do the students find most helpful? How can these courses be customized to better serve the students? The purpose of this study is to interview students from a number of community colleges, exploring these topics from the student perspective with the goal of orientation course enhancement. Although students reported the skills and information pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…The curricular "tools" of the programs, in the form of college success skills and academic planning, which receive a great deal of attention in practice and in the literature, were only marginally related to engagement, and only in terms of one of the three kinds of engagement. These results are a counterpoint, or at least a complement, to the literature that emphasizes the critical role of study skills, time management, and related competencies in college curricula (Allan & Clarke, 2007;Duggan & Williams, 2010;Engstrom & Tinto, 2008;Robbins et al, 2004;Struthers, Perry, & Menec, 2000).…”
Section: Curricular Featuresmentioning
confidence: 64%
“…The curricular "tools" of the programs, in the form of college success skills and academic planning, which receive a great deal of attention in practice and in the literature, were only marginally related to engagement, and only in terms of one of the three kinds of engagement. These results are a counterpoint, or at least a complement, to the literature that emphasizes the critical role of study skills, time management, and related competencies in college curricula (Allan & Clarke, 2007;Duggan & Williams, 2010;Engstrom & Tinto, 2008;Robbins et al, 2004;Struthers, Perry, & Menec, 2000).…”
Section: Curricular Featuresmentioning
confidence: 64%
“…The broad reach of these two latent classes confirms the multiple and overlapping terms that researchers use to variously define success courses in the literature (e.g. Duggan and Williams 2010;O'Gara et al 2009), even as a distinction between skillsfocused and comprehensive programs shows through.…”
Section: ) Minimalist Programsmentioning
confidence: 81%
“…Qualitative research on student success courses provides some insights into students' experiences. For example, Duggan and Williams (2010) interviewed 60 students who recently had taken a student success course at one of ten community colleges, seeking to determine the topics and teaching methods that students perceived to be most helpful. While most students reported that their student success course was useful, some said they did not need the course because they perceived themselves to be sufficiently prepared for college prior to the course or believed that the information provided was "common sense" (Duggan and Williams 2010, p. 125).…”
Section: Programs and Initiatives With Potential To Improve Adult Students' Outcomesmentioning
confidence: 99%